Nonverbal Communication Analysis in Animated Series Grizzy and Les Lemmings ÔÇô Battle Musicale ÔÇô Episode 223 - Ramadhani, Yessi; Lani, Ristika (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Grizzy and Les Lemmings animated film is a French computer- animated television series produced by Studio Days with France Televisions and Boomerang. The animation is a silent comedy animation that focuses on a grizzly bear, named Grizzy who is a brown bear living in a tree house. Grizzy always has to deal with a herd of lemmings that always annoy him. Lemmings are a type of mouse that digs holes. They mainly live in the eastern hemisphere. In winter, it is white as snow, and in warm season, it becomes gray and brown. Grizzy and Les Lemmings Battle Musicale episode 223 animation in this episode of the warm season so the lemmings are gray. In this episode, it tells the story of a group of lemmings who are dancing and swaying while listening to music from the radio at Grizzy's house. Grizzy also likes the music from the radio, so there is a fight over the radio between Grizzy and a group of lemmings. When the struggle occurred, the radio was damaged so that the chip stuck to a blue parrot which caused the parrot to make a sound like the radio. The researcher uses Nonverbal Communication Theory which means the exchange and delivery of messages that do not use words using more body gestures, expressions, gestures, body movements, tone intonation, eye contact, proximity and touch. Grizzy also liked the music from the radio, so there was a fight over the radio between Grizzy and a group of lemmings. When the struggle occurred, the radio was damaged so that the chip stuck to a blue parrot which caused the parrot to make a sound like the radio. The researcher uses Nonverbal Communication Theory which means the exchange and delivery of messages that do not use words using more body gestures, expressions, gestures, body movements, tone intonation, eye contact, proximity and touch. Grizzy also liked the music from the radio, so there was a fight over the radio between Grizzy and a group of lemmings. When the struggle occurred, the radio was damaged so that the chip stuck to a blue parrot which caused the parrot to make a sound like the radio. The researcher uses Nonverbal Communication Theory which means the exchange and delivery of messages that do not use words using more body gestures, expressions, gestures, body movements, tone intonation, eye contact, proximity and touch